Os informantes da polícia política e o anticomunismo durante a ditadura civil-militar (Paraná, 1964-1985) - Silva, Rodrigo Pereira da (2017)
This work aims to analyze the performance and the collaboration of the "informers" linked or not to the Paraná State Political Police between the years 1964 to 1985. This timeframe covers the period of the civil-military dictatorship in Brazil, started on March 31, 1964 with a coup d'état articulated between sectors of civil society and military. We seek to analyze - through reports, information, narratives, tickets, letters, crafts, etc., produced and/or received by the Precinct of Political and Social Order of Paraná (PPSO/PR) - the influence exercised by the anticommunist imaginary propagated and disseminated at the time, both by civil and military sectors, over the denunciations practiced by informers who, apparently moved much more by their political passions than in exchange for purely material interests (money, ease, for the pursuit of certain activities, etc.) used to appropriated of such discourse and disseminated it through its denunciations as a form of maintenance of the stability of the public order and prevention of the dissemination in the social Paraná branch of the communist ideology